Phallic minarets and masculine subjectivity in Ahmad Fuadiâ€™s Negeri 5 Menara: DaniÃ©louian lingga and Lacanian phallocentrism perspectives - Moh Atikurrahman; Wahidah Zein Br. Siregar (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This article explores the phallic and patriarchal imaginaries structuring Ahmad Fuadiâ€™s widely celebrated Islamic Bildungsroman Negeri 5 Menara. Focusing on the recurrent motif of the minaret and other vertical architectures, this study reads these structures as a chain of lingga-like monuments that concentrate male creativity, religious aspiration, and class ascent, while rendering female figures structurally marginal. The analysis builds on a qualitative close reading of the novelâ€™s narrative, triangulating DaniÃ©louâ€™s conception of the lingga as sacred sign of male creative power with Lacanian concept of the phallus as empty signifier, the formation of subjectivity, and phallogocentrism. Through this lens, Alif Fikri and the Sahibul Menara emerge as paradigmatic subjects whose desires, failures, and eventual success are organised around the minaret as symbolic centre, whereas womenâ€”Amak, Alifâ€™s sister, and other peripheral figuresâ€”are confined to what the one-sex model and phallic norm encode as remainder, lack, or abject. The article shows that, beneath its inspirational rhetoric of â€œMan Jadda Wajadaâ€ and its celebration of perseverance, Negeri 5 Menaraquietly reproduces a long-standing pattern in Indonesian prose whereby the project of â€œbuilding civilisationâ€ is reserved for masculine bodies aligned with the phallus. This article reframes a widely acclaimed pesantren novel as a key site for rethinking gendered subjectivity, Islamic schooling, and class formation in contemporary Indonesian literature.